Switching Behaviour of Non Muslim Costumers to Indonesian Islamic Bank at The Jombang Branch - Bekti Widiyaningsih; Laila fatikhatul ula; Mustamim Mustamim (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the behavior of switching non-Muslim customers of Indonesian Islamic Bank Jombang bracnh office. The method used in this study is descriptive qualitative using primary data. Primary data is data obtained directly from research subjects and directly related to the problems studied, while secondary data collected from books, journals, and documents/reports that have been available. Results of the study obtained are to find out what are the reasons for customers to switch behavior from conventional banks to islamic banks in Jombang branch offices, non-Muslim customers who switch in terms of profit-sharing and deposits. This research shows that Non-Muslim customers from BCA Bank switch to BSI Bank with the nominal amount above 100th million within 1st year with an agreement (revenue sharing). To find out the factors that cause the switching behavior of non-Muslim customers in Islamic banks jombang (BSI), factors that cause customers to switch in terms of Rade (Interest Rate), sales promotion and price of financing, and know the agreement and its influence on non-Muslim customers in deciding switching behavior, non-Muslim customers do not care about the contract because all they know is credit with interest then Rate.